IT COMMUNITY SERVICE BY UKI TORAJA FOR THE INTERNATIONAL STUDENTS - Michael, Aryo; Garoga, Melki; Maharani, Fanny (Jurnal Literasiologi, 2024)
Connecting Cultures: IT Community Service by UKI Toraja for International Students. This was achieved through the use of cutting edge science and technology, enabling smooth communication could take place between the UKI Toraja community with international students. The project was approached using diverse techniques, adopting digital communication and collaboration tools as an ad hoc solution to interactive learning platforms, multimedia content creation resources along with data visualization of large corpora. Over the four months of community members participating in this program, 21 international school students participated with many noting improved levels and that they felt like a part of their new local home. This work shows innovation is successful in using technology-based solutions to create inclusive, supportive environments for our diverse students.